Zum Zusammenhang zwischen Größe und Wachstum bei Gründungen - Empirische Ergebnisse für West-Deutschland - Eric A. Nerlinger; Matthias Almus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
The present paper deals with the question whether 'Gibrat's law' is applicable to firms founded between 1989 and 1996 within the Western German manufacturing sector or not. The underlying assumption is that size of a firm has no in uence on its growth. Growth is rather determined by a process of random in uences. Within the context of the econometric analyses conducted in the present study, firms are subdivided into innovative and non-innovative young firms. A method introduced in Chesher (1979) is used to explore 'Gibrat's law' in order to examine the influence of firm size on growth. Moreover we test whether the growth process of firms remains stable over time or not. This so-called 'persistence of growth'-hypothesis implies that growth in one period has an impact on growth in the following period. Using data from the ZEW-Foundation Panel (West), 'Gibrat's law' is rejected for the group of innovative as well as for the group of non-innovative young firms in all periods examined. This confirms the results of a number of empirical studies over the last years, indicating that smaller firms have larger growth potential than larger ones.
Keywords: L60; L11; 330; Young Innovative Firms; New Technology-based Firms (NTBFs); Employment Growth; Gibrat's Law; Unternehmensgründung; Unternehmenswachstum; Betriebsgröße; Schätzung; Deutschland; Alte Bundesländer; Gibrat's Law